Sinensetin Reduces Osteoarthritis Pathology in the Tert-Butyl Hydroperoxide-Treated Chondrocytes and the Destabilization of the Medial Meniscus Model Mice via the AMPK/mTOR Signaling Pathway - Zhou, Wenxian; Shi, Yifeng; Wang, Hui; Yu, Caiyu; Zhu, Huanqing; Wu, Aimin (Frontiers in Pharmacology, 2021)
As a common degenerative disease, osteoarthritis (OA) usually causes disability in the elderly and socioeconomic burden. Previous studies have shown that proper autophagy has a protective effect on OA. Sinensetin (Sin) is a methylated flavonoid derived from citrus fruits. Studies have shown that Sin is a good autophagy inducer and has shown excellent therapeutic effects in a variety of diseases; however, its role in the treatment of OA is not fully understood. This study proved the protective effect of Sin on OA through a series of in vivo and in vitro experiments. In vitro experiments have shown that Sin may inhibit chondrocyte apoptosis induced by tert-butyl hydroperoxide (TBHP); at the same time, it might also inhibit the production of MMP13 and promote the production of aggrecan and collagen II. Mechanism studies have shown that Sin promotes chondrocyte autophagy by activating AMPK/mTOR signaling pathway. On the contrary, inhibition of autophagy can partially abolish the protective effect of Sin on TBHP-treated chondrocytes. In vivo experiments show that Sin may protect against DMM-induced OA pathogenesis. These results provide evidence that Sin serves as a potential candidate for the treatment of OA.